The problem of training economists in scientific and pedagogical theory - Zagorodnya, Alla (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
he article analyzes the problems of professional training of the economic sector that recorded in pedagogical theory. The essence of the problem and features professional training Economic sectors that studied in various aspects in the context of the study of the history and nature of the educational process in schools of all levels and types is economic orientation. The analysis of scientific and theoretical sources that indicate different directions, multidisciplinary focus and comprehensiveness age contingent investigated the problem of forming specialists in economics. Considered professional orientation training future economists from different models of professional training of the economic sector in higher educational institutions of Ukraine. Pedagogical conditions that ensure professional orientation training based on interdisciplinary connections: implementation of the principle mizhpredmetnosti in the content curriculum (content of training programs provided two components: the required and optional); improving methods of training sessions (simulation of problem situations of economic content, including a lecture solve applied problems, the economic interpretation of certain mathematical concepts), providing independent interdisciplinary orientation of teaching and learning of students (including in individual tasks and homework economic content, writing scientific essays on economic subjects), the integration of mathematical and economic subjects by means of information technology (development of mathematical problems of economic content, which can be solved by computer means introduction in the educational process and laboratory studies binary).